Connecting the dots: Sector coupling and hydrogen policies in Europe - Belova, Arina (Masaryk University Press, 2023)
Not long ago, energy policy used to be neatly compartmentalized into individual industries. Transportation, power generation, heat production, and so on each had their own distinct material structure, rules, and behavior-governing norms and practices. With rising climate change concerns, energy policy has effectively merged with climate policy and the transition to low-carbon energy has become a priority. This paradigm shift has spurred rapid technological development, introduced new rules and practices and generally redefined the energy landscape. Along the way, the existing borders between industries were disrupted as the decarbonization of one tends to be closely tied with the decarbonization of others. The construction of an all-encompassing integrated energy system is now underway. Conceptually, this process has been understood as "sector coupling", i.e., bringing individual industries closer together to optimize the energy transition as well as the deployment of enabling technologies such as energy storage and hydrogen. This book is intended to reflect on this process. Specifically, it inquiries what is sector coupling and how is it understood across different political and analytical contexts? What role will hydrogen play in the development of sector coupling? What are the current and expected hydrogen policies in Europe, USA, and China? The results show that the understanding of sector-coupling has evolved over time and varies across policy contexts. The role of hydrogen in sector-coupling is uncertain in the future due to production and utilization issues, with some potential sources of demand being rapidly electrified without an intermediate step of hydrogen production and combustion. Hydrogen technologies are currently being developed primarily in Europe, but this may soon change as the US and China gradually introduce more ambitious targets and more interesting support programs. Finally, the publication presents the development pathways of hydrogen technologies in different national contexts and pins down the future crossroads at which the shape of sector coupling and the hydrogen economy will be decided.